PENGEMBANGAN KURIKULUM 2013 DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 1 PANARUKAN SITUBONDO 2013/2014 - Mory Victor Febrianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2016)
This study aims to examine the development of Curriculum 2013 in the learning of Islamic Education and Budi Pekerti at SMAN 1 Panarukan Situbondo which includes: Planning Learning Islamic Religious Education and Character In Curriculum 2013 in SMA Negeri I Panarukan. Implementation of Islamic Education Learning and Character Budi In Curriculum 2013 in SMA Negeri I Panarukan. Evaluation of Islamic Religious Education Learning and Character Budi In Curriculum 2013 at SMA Negeri I Panarukan. This research uses qualitative research. The conclusion of this research is first, the implementation of learning plan of Islamic Education and Budi Pekerti on the curriculum of 2013 covering annual program, semester program, weekly and daily program, remedial program and enrichment of both implementation of learning of Islamic Education and Character Budi on Curriculum 2013 covering the development of intimacy and pree test, the formation of competence, and post test, the third implementation of evaluation of learning of Islamic Education and Character Budi on Curriculum 2013 include assessment of attitude competence, knowledge competency assessment, and skill assessment. But in general the development of Curriculum 2013 on learning Islamic Religious Education and Character in SMAN 1 Panarukan seen from the planning system, the implementation is maximal but the assessment system is still less than the maximum